2006
DOI: 10.1152/ajpgi.00079.2006
|View full text |Cite
|
Sign up to set email alerts
|

Luminal glucose sensing in the rat intestine has characteristics of a sodium-glucose cotransporter

Abstract: The presence of glucose in the intestinal lumen elicits a number of changes in gastrointestinal function, including inhibition of gastric emptying and food intake and stimulation of pancreatic and intestinal secretion. The present study tested the hypothesis that Na(+)-glucose cotransporter (SGLT)-3, a member of the SGLT family of transport proteins, is involved in detection of luminal glucose in the intestine. Gastric emptying, measured in awake rats, was significantly inhibited by perfusion of the intestine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 31 publications
(36 reference statements)
1
68
0
Order By: Relevance
“…This possibility made us explore SGLT3, another putative glucose sensor. SGLT3 is a neuronally located member of the solute carrier family of proteins that appears to function as a sensor rather than a transporter of glucose (6,10). Binding of glucose (but not saccharin) to SGLT3 leads to membrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility made us explore SGLT3, another putative glucose sensor. SGLT3 is a neuronally located member of the solute carrier family of proteins that appears to function as a sensor rather than a transporter of glucose (6,10). Binding of glucose (but not saccharin) to SGLT3 leads to membrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that vagal afferents may be detecting nutrient delivery, for example, through activation of SGLT1 or SGLT3 (12,17), intestinal sweet taste receptors such as T1R3 (23), or portal/hepatic glucoreceptors (26,32). An output pathway then leads to upregulation of SGLT protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…43) on the tongue insofar as the process of transporting molecules (in this case glucose and Na) into the enterocyte (or entero-endocrine cell) is also the event that depolarizes the cell (21). However, these transporters are highly specific to glucose and their effects appear to be sensory, insofar as nonmetabolizable glucose analogues likewise stimulate these transceptors (11,24). Previous studies on glucose transport have suggested that initial activity at the SGLTs (but also GLUTs) depolarizes the cell and, in doing so, activates nearby T1Rs (for a review see Ref.…”
Section: Methodsmentioning
confidence: 99%